Ellie and the cat - Blackman, Malorie (Cassava Republic Press, 2008)
This is a story about a girl called Ellie who is the most spoilt and rudest child you could ever meet. She goes to visit her Grandma on holiday but little does she know she is in for a surprise which will teach her to change her ways.
Keywords: Fiction; Juvenile Literature